MENINGKATKAN KINERJA GURU MELALUI KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DI UPT SMP NEGERI 42 MEDAN KECAMATAN MEDAN DELI TAHUN PELAJARAN 2017/2018 - Jamal Husein Harahap (Universitas Islam Negeri Sumatera Utara Medan, 2022)
The purpose of this study was to determine the managerial strategy of school principals in improving teacher performance at UPT SMP Negeri 42 Medan, Medan Deli District, for the 2017/2018 academic year. 2017/2018 Academic Year. The research method used was descriptive research. This research was conducted at UPT SMP Negeri 42 Medan, Medan Deli District. The time for carrying out the research was from January to March 2018. Data collection techniques were in the form of observation, interviews and documentation. The results of this study showed that the strategy carried out by the principal in improving the performance of teachers at UPT SMP Negeri 42 Medan, Medan Deli District, can be seen from the aspects of planning, organizing, implementing and supervising the principal in improving teacher performance, namely through the principal's strategy in tying performance teachers make teachers there good, orderly and disciplined in carrying out their duties such as being absent, entering class, and the principal includes teachers in various education and training, activates the MGMP forum, provides the necessary facilities and supervises, encourages/directs it turns out to be effective. The managerial ability of the school principal in improving teacher performance is seen from the planning, organizing, implementing, monitoring and evaluation aspects that have been made by the school principal where the results have not been maximized. Managerial principals in improving teacher performance have been carried out as planned but the results have not been as expected.